Maternal and Child Health Interventions: A Bibliometric Assessment of Global Research Landscape - Yocki Yuanti; Erny Elviany Sabaruddin; Dewi Rostianingsih (West Science Interdisciplinary Studies, 2023)
Maternal and child health interventions play a pivotal role in improving health outcomes and promoting well-being among mothers and children worldwide. This study employs a multidimensional approach, combining bibliometric analysis, clustering, and citation analysis, to assess the global research landscape of maternal and child health interventions. The research methodology involves systematic data collection, preprocessing, and the utilization of VOSviewer for visualization and analysis. The results reveal thematic clusters, high-impact studies, and prevailing research trends within the field. The identified clusters encompass diverse themes such as child development, adolescent health, and policy implications. High-impact studies emphasize evidence-based approaches, addressing maternal undernutrition, child health interventions, and maternal and newborn health. Additionally, the frequency of keywords reflects research priorities in coverage, child health interventions, and intervention effectiveness. Conversely, areas with fewer occurrences, such as infant health and child undernutrition, suggest potential research gaps. This comprehensive assessment of the maternal and child health interventions landscape informs evidence-based decision-making, identifies research priorities, and guides the development of holistic interventions. The study contributes to advancing maternal and child health outcomes globally by providing insights into the current state, gaps, and directions for future research.